A One Precursor One siRNA Model for Pol IV-Dependent siRNA Biogenesis - Zhai, Jixian; Bischof, Sylvain; Wang, Haifeng; Feng, Suhua; Lee, Tzuu-fen; Teng, Chong; Chen, Xinyuan; Park, Soo Young; Liu, Linshan; Gallego-Bartolome, Javier; Liu, Wanlu; Henderson, Ian R.; et al. (Cell, 2015)
RNA-directed DNA methylation in Arabidopsis thaliana is driven by the plant-specific RNA Polymerase IV (Pol IV). It has been assumed that a Pol IV transcript can give rise to multiple 24-nt small interfering RNAs (siRNAs) that target DNA methylation. Here, we demonstrate that Pol IV-dependent RNAs (P4RNAs) from wild-type Arabidopsis are surprisingly short in length (30 to 40 nt) and mirror 24-nt siRNAs in distribution, abundance, strand bias, and 5′-adenine preference. P4RNAs exhibit transcription start sites similar to Pol II products and are featured with 5′-monophosphates and 3′-misincorporated nucleotides. The 3′-misincorporation preferentially occurs at methylated cytosines on the template DNA strand, suggesting a co-transcriptional feedback to siRNA biogenesis by DNA methylation to reinforce silencing locally. These results highlight an unusual mechanism of Pol IV transcription and suggest a “one precursor, one siRNA” model for the biogenesis of 24-nt siRNAs in Arabidopsis. [Display omitted] •Pol IV transcribes 30 to 40 nucleotide short RNAs to initiate siRNA biogenesis•P4RNAs mirror siRNAs in distribution, abundance, strand bias and 5′-A preference•P4RNAs feature TSSs similar to Pol II products•P4RNAs carry 3′-misincorporation that preferentially occurs at methylated cytosines In contrast to the assumption that one Pol IV transcript gives rise to multiple siRNAs, it is now shown that Pol IV transcribes 30- to 40-nt short RNAs that are further processed to generate 24-nt mature products, thereby demonstrating a “one precursor, one siRNA” model for Pol IV-dependent siRNA biogenesis in Arabidopsis.